2021
DOI: 10.2174/2772434416666211111105854
|View full text |Cite
|
Sign up to set email alerts
|

Multipotentiality of Luliconazole against Various Fungal Strains: Novel Topical Formulations and Patent Review

Abstract: Background: Luliconazole is a broad-spectrum antifungal agent with impactful fungicidal and fungistatic activity. It has shown exceptional potency against miscellaneous fungal strains like Candida, Aspergillus, Malassezia, Fusarium species and various dermatophytes. Objective: Luliconazole belongs to class Ⅱ of the Biopharmaceutical Classification System with low aqueous solubility. Although it is available conventionally as 1% w/v topical cream, it has limitations of lower skin permeation and shorter skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, the clinical limitation of lower skin penetration and shorter skin retention time was need to be considered. A recent study showed nanoparticles based on various polymers can be used to overcome barriers of topical delivery and efficacy of LULI 34 . LULI has great potential in the treatment of various fungal infections, while further studies are needed to confirm the therapeutic effect on sporotrichosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical limitation of lower skin penetration and shorter skin retention time was need to be considered. A recent study showed nanoparticles based on various polymers can be used to overcome barriers of topical delivery and efficacy of LULI 34 . LULI has great potential in the treatment of various fungal infections, while further studies are needed to confirm the therapeutic effect on sporotrichosis.…”
Section: Discussionmentioning
confidence: 99%